2022
DOI: 10.1128/spectrum.01913-22
|View full text |Cite
|
Sign up to set email alerts
|

The Bombyx mori Nucleopolyhedrovirus GP64 Retains the Transmembrane Helix of Signal Peptide to Contribute to Secretion across the Cytomembrane

Abstract: BmNPV is the primary pathogen of silkworms, which causes severe economic losses in sericulture. BmNPV and Autographa californica multiple nucleopolyhedrovirus (AcMNPV) are closely related group I alphabaculoviruses, but they exhibit nonoverlapping host specificity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…Our previous studies revealed that BmNPV BV infection was different from that of AcMNPV, including direct membrane fusion that caused nucleocapsid transportation failure to the nucleus [20], the exact cause that BmNPV failure to infect nonhost cells [9]. BmNPV GP64 retained its SP in the mature virion [10], and this uncleaved SP determined BmNPV's special dependence on cholesterol in the virus infection process [11,21]. Viral proteins and host proteins in the envelope play important roles in the BV infection process, hereby, proteomics composition analysis of the BV envelope will facilitate the understanding of BmNPV budding and infection process.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our previous studies revealed that BmNPV BV infection was different from that of AcMNPV, including direct membrane fusion that caused nucleocapsid transportation failure to the nucleus [20], the exact cause that BmNPV failure to infect nonhost cells [9]. BmNPV GP64 retained its SP in the mature virion [10], and this uncleaved SP determined BmNPV's special dependence on cholesterol in the virus infection process [11,21]. Viral proteins and host proteins in the envelope play important roles in the BV infection process, hereby, proteomics composition analysis of the BV envelope will facilitate the understanding of BmNPV budding and infection process.…”
Section: Discussionmentioning
confidence: 99%
“…BmN cells were cultured at 27 ℃ using standard techniques in TC-100 insect medium (AppliChem, Darmstadt, Germany) supplemented with 10% FBS (Gibco BRL, Gaithersburg, MD, USA). BmBac Δgp64 -gp64 (vGP64) and BmBac Δgp64 -SP ∆n gp64 (vSP ∆n GP64) were previously constructed by Hao et al [10,11]. In brief, BmNPV gp64 gene in BmBacmid was replaced with chloramphenicol to generate gp64-null bacmid (BmBac Δgp64 ) [12], then wildtype gp64 was reintroduced into the polyhedrin locus of BmBac Δgp64 by transposition to generate BmBac Δgp64 -gp64 [10].…”
Section: Cells and Viruses Amplificationmentioning
confidence: 99%
See 3 more Smart Citations